Enigmatic Ladies of the Rings: How Cohesin Dysfunction Affects Myeloid Neoplasms Insurgence - Pezzotta, Alex; Mazzola, Mara; Spreafico, Marco; Marozzi, Anna; Pistocchi, Anna (Frontiers in Cell and Developmental Biology, 2019)
The genes of the cohesin complex exert different functions, ranging from the adhesion of sister chromatids during the cell cycle, DNA repair, gene expression and chromatin architecture remodelling. In recent years, the improvement of DNA sequencing technologies allows the identification of cohesin mutations in different tumours such as Acute Myeloid Leukemia (AML), Acute Megakarioblastic Leukemia (AMKL) and Myelodysplastic Syndromes (MDS). However, the role of cohesin dysfunction in cancer insurgence remains elusive. In this regard, cells harbouring cohesin mutations do not show any increase in aneuploidy that might explain their oncogenic activity, nor cohesin mutations are sufficient to induce myeloid neoplasms as they have to co-occur with other causative mutations such as NPM1, FLT3-ITD and DNMT3A. Several works, also using animal models for cohesin haploinsufficiency, correlate cohesin activity with dysregulated expression of genes involved in myeloid development and differentiation. These evidences support the involvement of cohesin mutations in myeloid neoplasms.